Analysis of anti‐tumour necrosis factor‐induced skin lesions reveals strong T helper 1 activation with some distinct immunological characteristics. (1st May 2018) - Stoffel, E.; Maier, H.; Riedl, E.; Brüggen, M.‐C.; Reininger, B.; Schaschinger, M.; Bangert, C.; Guenova, E.; Stingl, G.; Brunner, P.M.
Summary: Background: Psoriasiform and eczematous eruptions are the most common dermatological adverse reactions linked to anti‐tumour necrosis factor (TNF)‐α therapy. Yet, a detailed characterization of their immune phenotype is lacking. Objectives: To characterize anti‐TNF‐α‐induced inflammatory skin lesions at a histopathological, cellular and molecular level, compared with psoriasis, eczema (atopic dermatitis) and healthy control skin. Methods: Histopathological evaluation, gene expression (quantitative real‐time polymerase chain reaction) and computer‐assisted immunohistological studies (TissueFAXS) were performed on 19 skin biopsies from patients with inflammatory bowel disease ( n = 17) and rheumatoid arthritis ( n = 2) with new‐onset inflammatory skin lesions during anti‐TNF‐α‐therapy. Results: Although most biopsies showed a psoriasiform and/or spongiotic (eczematous) histopathological architecture, these lesions were inconsistent with either psoriasis or eczema on a molecular level using an established chemokine (C‐C motif) ligand 27/inducible nitric oxide synthase classifier. Despite some differences in immune skewing depending on the specific histopathological reaction pattern, all anti‐TNF‐α‐induced lesions showed strong interferon (IFN)‐γ activation, at higher levels than in psoriasis or eczema. IFN‐γ was most likely produced by CD3/CD4/Tbet‐positive T helper 1 lymphocytes. Conclusions: New‐onset anti‐TNF‐α‐induced eruptions previously classified as psoriasis or spongiotic dermatitis (eczema) exhibit a molecular profile that is different from either of these disorders.